Antibacterial and Antifungal Activities of Pandanus amaryllifolius Leaf Extract, Fractions, and Isolate and Their Role in Anti-Dandruff Shampoo Optimization - Wijayanti, Rina; Susmayanti, Windi; Meliana, Dias Feni; Fauziyah, Afifah Husnun; Anjeline, Aprilia Mega; Putri, Devyra Yunika Mutiara Sari Suwarto; Ulya, Fadhia Tafrichatul (Sciences of Pharmacy, 2025)
Pandan leaves (Pandanus amaryllifolius Roxb.) possess various biological activities due to their secondary metabolites, including flavonoids, alkaloids, phenolics, saponins, and triterpenoids/steroids. This study aimed to evaluate the antibacterial and antifungal activities of pandan leaf extracts, fractions, and isolates against Staphylococcus aureus, Escherichia coli, and Pityrosporum ovale, as well as to optimize surfactants in shampoo formulations. The experimental design used a post-test-only control group. Samples were processed through maceration, followed by fractionation and isolation using the KLT-P method. Antibacterial and antifungal activities were assessed using the agar well diffusion method. The most effective antibacterial activity against E. coli was observed in the n-hexane isolate at 700 ppm, with an inhibition zone of 19.6 mm, classified as strong. For S. aureus, the 100% water fraction produced an inhibition zone of 9.96 mm, classified as weak. The ethanol extract showed antifungal activity against P. ovale with an inhibition zone of 6.29 mm, categorized as moderate. Shampoo formulation optimization using sodium lauryl sulfate and cocamide DEA resulted in an ideal ratio of 0.235 to 0.764. This combination produced a shampoo with acceptable physical characteristics, including a pH of 5.71, foam height of 2.56 cm, and viscosity of 899.9 cps, all of which met the standard requirements.